Penegakan Hukum Atas Pelanggaran Konten Digital Ditinjau Dari Hukum Positif Di Indonesia - PUTU EKA TRISNA DEWI (INVENTION: Journal of Intellectual Property Law, 2025)
Today's society cannot be separated from the development and progress in the field of science and technology. This progress makes it easier for people to gain access and distribute content through social media, streaming sites, and other digital platforms. Digital content such as music, films, e-books, and graphic designs are vulnerable to duplication, distribution, and reuse without permission. This study aims to analyze the form of norm conflict between the two laws, especially in the practice of blocking content by the government through the Ministry of Communication and Information (Kominfo). This research method uses normative legal research, namely research that is based on literature reviews and analysis of written legal materials. The main focus of the study is the norm conflict between the Copyright Law and the ITE Law using a statute approach, a conceptual approach, and a case approach. The results of the study show that there is a procedural conflict between the principle of judicial proof in the Copyright Law and the administrative authority in the ITE Law. This conflict creates legal uncertainty, potential violations of digital rights, and the need for regulatory harmonization.